Economic Feasibility Analysis of Fishing Job Operation in Well YS13 - Muhammad Ariyon; Bella Santika; Fitrianti (UIR PRESS, 2022)
Oil consumption in Indonesia has increased from year to year. However, the increasing demand for oil and natural gas is inversely proportional to oil and gas production, which always declines from year to year. One of the factors causing the decline in production is the well damage. Well YS13 is a well that is damaged in the form of fish in the well. A fishing job is the most appropriate option to solve the problem of the presence of fish in the well because the fish in the well must be removed to continue well production activities or drilling activities. This study aimed to determine the economic feasibility of fishing job activities to be carried out at the YS13 well. The research begins with the preparation of the required data, then calculate the predicted production of the YS13 well with the decline curve method, estimates the cost of the fishing job, and economic fishing time (EFT). And determines the economic feasibility of the fishing job project by calculating profit indicators, namely Net Present Value (NPV), Internal Rate of Return (IRR), and Pay Out Time (POT). The results of calculations using the decline curve method obtained that the total production for 20 months is 4293.52 bbl. The EFT value is 3 days with Ps = 10% and the total cost of fishing is 28.657,70. The economic value of the project with discount rate = 12%, MARR = 12%, NPV = 147.367,20, IRR = 114%, and POT = 1.44. From the results of the calculation of the economic feasibility, the project is considered feasible to be carried out.